Penggunaan Urea sebagai Sumber Nitrogen pada Proses Biodegradasi Substrat Lumpur Sawit oleh Jamur Phanerochaete chrysosporium - Noferdiman, Noferdiman; Rizal, Yose; Mirzah, Mirzah; Heryandi, Yan; Marlida, Yetti (Fakultas Peternakan Universitas Jambi, 2008)
The research was conducted to study the biodegradation capability on palm oil sludge substrate by Phanerochaete chrysosporium with increasing urea as nitrogen source. The experiment was designed using Completely Randomized Design (CRD) with 5 treatments and 4 replications, namely : U-0 = 0,0 % Urea, U-1= 0,5 % Urea, U-2 = 1,0 % Urea, U-3 = 1,5 % Urea and U-4 = 2,0 % Urea. The observed variables were the amount of spore, C/N ratio, pH, crude fiber, crude protein, lignin, cellulose and enzyme activities. The result of this study showed that added urea were significantly (P<0.01) crude fiber, crude protein, lignin, cellulose and enzyme activities. The use of urea on the first level amounting to 1.5 % in palm oil sludge can help Phanerochaete chrysosporium to reduce crude fiber to (30,71%), lignin (29.89 %), cellulose (36.42 %) and it can increase the content of crude protein to (34.50 %), reduction sugar and enzyme activities.